Non-Technical Losses, Energy Efficiency and Conservative Methodology in the Electricity Sector of Nigeria: The Case of Calabar, Cross River State - Obafemi, Frances Ngozi; Ifere, Eugene Okoi (International Journal of Energy Economics and Policy, 2013)
Today’s challenge in electricity consumption in Nigeria is on how to use electricity wisely. Nigeria electricity sector is facing abnormal power supply situation, as demand outstrips supply, culminating in electricity supply-cum–demand imbalance. This owes to inefficiency and non technical losses which contributes to incessant power outages resulting in heavy economic losses and poor performance of the economy. This study investigates and identifies non-technical losses in the electricity sector occasioned by illegitimate activities. The methodology is a combination of quantitative and qualitative sample survey. The data set is a simple random sampling of households using electricity, and the number of units chosen was based on statistical power analysis. The result shows that energy wastage is from poor lighting attitudes, and choice of appliances. Implementation of efficient lighting attitudes is encouraged. Findings from the study if replicated will serve as a model for energy efficiency and methodology for the Nigeria Economy. Keywords: Non-Technical Losses; Energy Efficiency; Conservation JEL Classifications: Q43; C42; O55